A comparison of the growth and photosynthetic response of Vallisneria natans (Lour.) Hara to a long-term water depth gradient under flowing and static water. Issue 1 (1st January 2018) - Wei, Hua; He, Feng; Xu, Dong; Zhou, Qiaohong; Xiao, Enrong; Zhang, Liping; Wu, Zhenbin
ABSTRACT: In a mesocosm experiment, the growth and photosynthetic responses of Vallisneria natans (Lour.) Hara was studied monthly in different water depths under flowing and static water. Water depth showed a significant effect on the shoot length, below-ground: above-ground biomass, and total biomass, while water velocity showed only a significant effect on the total biomass. In addition, total biomass and shoot length at 45, 75 and 105 cm was higher in the flowing treatment than that in the static treatment, which suggested that total biomass and shoot length are promoted by water flow to some extent. All of the investigated photosynthetic showed different changes with different months. Water depth exhibited significant effects on the maximum photosynthetic efficiency Fv /Fm, the maximum electron transport rate rETRmax, Chl a, Chl a + b and Chl a / b, while water velocity showed only significant effects on Chl a, Chl a + b, ETRmax . The rapid light response curves varied differently with the time periods. In October, the time-course of slow chlorophyll a fluorescence induction curves, Fm peak, in the flowing treatment in 45, 75 and 105 cm is higher than that in the static treatment. All the results demonstrated that the differences between flowing and static water resulted in the different life strategy.